Productive pedagogical projects a tool for the teaching-learning process (Revista Sistemas de Producción Agroecológicos, 2018)
The objective of this work was to characterize and analyze the productive pedagogical projects (PPP) developed by the students of the professional teaching practice of the Bachelor program in Agricultural Production, during a period of three years in order to demonstrate the strengthening of the agricultural modality in the different educational institutions located in the department of Meta, Colombia. For the collection of information, databases of five educational institutions in the area were consulted, surveys were designed that were applied to students, practice advisors, parents and students in pedagogical practice (SPP) of the Universidad de los Llanos; meetings were also held with the SPP where they presented the projects in which they participated, there were evidenced the factors that influenced the impact generated by these projects in the different educational institutions, and likewise, was analyzed their benefit in the formation of SPP, both professionally and personally, and even in their families. It is concluded that these curricular actions in most cases strengthen thematic contents of the agricultural modality, therefore, their participation was dynamic for the success of the PPP, which affected the improvement of the quality of life of some families that participated, allowing to offer alternatives of food security and the strengthening of the productive processes in the institutions. Likewise, the practitioners stated that the exercise of professional teaching practice allows to develop skills, abilities, academic knowledge, and personal that are applied in the design, execution and evaluation of PPP, which is a preparation to address the challenges of the workplace.
Keywords: teaching practice; educational community; food security; family farming